Analisis Perbandingan Perkembangan Jumlah Perusahaan Asuransi Syariah Dengan Asuransi Konvensional di Indonesia Periode 2013-2022 - Lutfiah Nur Azizah; Wanda Nilam Sari Br. Harefa; Dhea Amanda; Mentari Syahputri Purba; Annisa Sanas Nalamjra; Agustin Mahardika Tampubolon; Desry Situngkir (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to find out how the development and comparison between Sharia Insurance & Conventional Insurance. The discussion focuses on seeing how the movement of the number of insurance companies. By using a comparative approach, the results of this study concluded that conventional insurance until the last year of research still dominated compared to Islamic insurance because conventional insurance was known by the community before Islamic insurance. As a result, it can be seen that Islamic insurance has a slower development compared to conventional insurance.Â